Alignment of Workforce Strategies with Business Values for Relationship Manager at a Branch Networking Organization - Sally Notariza Taher (Institute of Computer Science (IOCS), 2022)
Objectives: This research will assess a full-scope alignment between the activities of Relationship Manager, the design of performance score cards and their correlations to the value produced to the bank, and the rewards (compensation) received by RM. It is essential for the bank to have complete scope alignment to guarantee that activities will contribute to the achievement of bank-wide revenue targets and that RM will receive rewards in proportion to their contributions.“Alignment of Workforce Strategies with Business Values Framework”This starts from a phenomenon that occurs in branch network organisation in the banking industry, namely the decision to reward RM (Relationship Manager) which is calculated based on activity-based (RM activities in offering products) or value-based, namely revenue generated from the sale of banking products offered by RM. RM plays a key position in the branch network organization and serves as a point of contact between banks and their clients. This RM engages in activities such as the provision of banking products including deposits, insurance, investments, and account opening. If customers successfully acquire all of these products, the bank will get value in the form of revenue. To qualify as a value-based reward, RM compensation (rewards) must be computed as the total of the percentage of revenue. Method/Analysis: This research will focus on sales organizations with a branch network organisation in the banking industry. In order to provide systematic information about a phenomenon and to describe the current state of an identified variable, the analysis will first start with descriptive analysis, continue with correlational analysis to determine the extent of a relationship between two or more variables using statistical approach.Findings: The outcomes of the analysis indicate that RM activities have been governed into a scorecard, with Wealth Management having the largest weightage (50%) and having a significant correlation with business value (revenue). Consequently, we should be able to find a positive correlation between the overall score-card outcomes and the amount of revenue earned. The revenue that RM brings in is also strongly correlated with the rewards (compensation) that RM receives.